Early Devonian organic-walled phytoplankton and miospores from the Precordillera Basin of San Juan, Argentina: biostratigraphic and paleobiogeographic implications. (22nd December 2017) - García Muro, Victoria J.; Rubinstein, Claudia V.; Rustán, Juan José
ABSTRACT: The palynological assemblages of the Talacasto and Punta Negra formations, from the Argentinean Precordillera, were analysed. Marine phytoplankton is dominant in both stratigraphic units. ? Cymatiosphaera florida, Evittia sommeri, Palacanthus ledanoisii, Riculasphaera fissa, Schizocystia pilosa, Tysanoprobolus polykion and Winwaloeusia distracta are among the most age-significant phytoplankton species of the Talacasto Formation, while Amicosporites sp. cf. A. streelii, Dictyotriletes emsiensis Morphon, Dictyotriletes favosus and ? Knoxisporites riondae prove the most biostratigraphically significant miospore species. A Lochkovian to probably late Pragian age is interpreted based on the marine and terrestrial palynomorphs. The lower part of the Punta Negra Formation contains phytoplankton species such as Cordobesia oriental, Cordobesia uruguayensis, Duvernaysphaera stellata, Navifusa bacilla, Polyedryxium fragosulum and Pterospermella sp. cf. P. pernambucensis as well as the miospores Acinosporites sp. cf. A. lindlarensis and Apiculatasporites microconus, which suggests an early Emsian age. Taxa such as Cordobesia, Schizocystia and Winwaloeusia support affinities of the Argentinean assemblages with Gondwana.